Nursing management of a patient with oculomotor nerve paralysis caused by systemic lupus erythematosus (1例系统性红斑狼疮致动眼神经麻痹患者护理体会) - LI Yuncui (李运翠); TANG Ling (唐玲); HU Hairong (胡海荣); PENG Dan (彭丹); QI Wenjing (綦文婧) (中西医结合护理)
This paper summarized the whole process of nursing intervention for a patient with oculomotor paralysis caused by systemic lupus erythematosus. Responsible nurses were involved throughout the process, in which overall evaluation of disease condition, routine nursing management, auricular point needle combined with auricular point pressing therapy were carried out. Targeted nursing plan should be made based on the overall evaluation and Traditional Chinese Medicine syndrome differentiation, in order to improve the rehabilitation of the patient. (本文总结1例系统性红斑狼疮(SLE)致动眼神经麻痹患者的护理经验, 包括整体评估、常规护理、耳针联合耳穴贴压等, 根据患者的评估结果和中医辨证, 制定针对性的护理方案, 有助于促进患者康复。)